Politeness strategy used by President Barack Obama speech - Putri Anzeli Simangunsong; Christina N Saragi; Kammer Sipayung (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Politeness strategy is a behavior that shows a friendly attitude in communicating with others, thus creating a good relationship. The purpose of this research is to find out the types of politeness strategies and the most dominant type contained in Obama's speech. The research design in this study is descriptive qualitative research. The data were taken from Barack Obama's speech. The results of data analysis show that there are 124 utterances containing politeness strategies to be analyzed in this study. There are four types of politeness strategies in Barack Obama's speech, namely Bald on record (10%), positive politeness (59%), negative politeness (10%), and off record (21%). The four types found are realized into twenty-five sub-categorizations, namely: Allow something, Greetings and Farewells, Detect the listener’s (Interests, wants, needs, and goods), Exaggerate (Interest, Approval, Sympathy listener), Engage listeners by telling a good story, Ask for approval, Avoid Disputes, Increase and emphasize community equality, The speaker knows and cares about the listener's wishes, Offers and Appointments, Be optimistic, Give or ask for reasons, Assumptions or claims of reciprocity, Be conventionally indirect, Be Pessimistic, Minimize Coercion, Give Respect, Impersonality of Speaker and Listener, Providing Relevant Cue Instructions, Overstate, Use Tautology, Be Ambiguous, Being Vague, Over – Generalize.